(untitled) (CAHIERS MAGELLANES-NS, 2024)
This paper delves into the humor embedded in Stephen Leacock's literary works, focusing on his masterful use of situational and character-based techniques. Leacock, a prolific Canadian humorist, adeptly combines everyday scenarios with vivid character portrayals to elicit laughter and provoke thought. By examining a selection of his short stories and essays, this study highlights how Leacock constructs humorous narratives through the interplay of absurd situations and the idiosyncrasies of his characters. The analysis begins with an exploration of situational humor, where Leacock creates comedic effects by placing characters in unexpected and often exaggerated predicaments. These situations reveal the absurdity of social norms and human behavior, providing a lens through which readers can reflect on their own lives. The paper then transitions to character-based humor, showcasing Leacock's ability to craft memorable and quirky personalities. His characters, often caricatures of societal archetypes, serve as vehicles for satire and social commentary. Through a close reading of selected texts, this study demonstrates Leacock's unique approach to humor, emphasizing the symbiotic relationship between situation and character. By blending these elements, Leacock not only entertains but also offers insightful critiques of contemporary society. This paper aims to contribute to the understanding of humor in literature and reaffirm Stephen Leacock's place as a seminal figure in the realm of comedic writing.